New employment actors: developments from Australia (Frankfurt am Main, 2008)
"This volume contains a selection of papers which go back to a conference on new employment actors, held at the University of Sydney in November 2006. The book contends that employment relations must be broadened to examine the new actors and processes and the role these play in the regulation and experience of work. It demonstrates this in the context of recent developments in Australia. In addition, the contributions evaluate the extent to which new employment actors either reinforce or replace the activities of the more established trade union, management, and state-based actors. It is argued that an inclusion of these new actors and processes is a more comprehensive way of understanding and explaining industrial society in the 21st century."